1963
DOI: 10.1002/app.1963.070070516
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the oxidative degradation of polyacrylonitrile using infrared spectroscopy

Abstract: The oxidative thermal degradation of polyacrylonitrile has been examined using infrared spectroscopy. It was found that the generally accepted mechanism for the thermal degradation of polyacrylonitrile in air, which involves direct interaction of neighboring nitrile groups, and alternate proposals, involving azomethine crosslinks through reaction of the nitrile group and a neighboring tertiary hydrogen atom, do not satisfactorily represent an initial degradation scheme accounting for the observed infrared spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

1969
1969
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(29 citation statements)
references
References 11 publications
2
26
0
1
Order By: Relevance
“…Conley and Beron [93] stated that two dominant peaks, which are at 2940 cm À1 and 2240 cm À1 start decreasing at 180 C due to the formation of cyclization reaction. However, Colemen and coworkers [94e99] suggested that the Fig.…”
Section: Infrared (Ir) Characteristicsmentioning
confidence: 98%
“…Conley and Beron [93] stated that two dominant peaks, which are at 2940 cm À1 and 2240 cm À1 start decreasing at 180 C due to the formation of cyclization reaction. However, Colemen and coworkers [94e99] suggested that the Fig.…”
Section: Infrared (Ir) Characteristicsmentioning
confidence: 98%
“…The nitrile groups (CN stretching vibration at ∼2240 cm −1 ) presented in untreated PAN evolve to CN (stretching vibration at ∼1600 cm −1 ) and/or CC bonds (stretching vibration at ∼1650 cm −1 ) generally conjugated to the last one during stabilization process, as shown in Figure . Highly stabilized PAN generally presents a very low intensity of band attributed to nitrile group and a moderate or strong absorption of CN and CC around 1600 cm −1 and CH at 800 cm −1 …”
Section: Introductionmentioning
confidence: 99%
“…Most authors have been in agreement that the initial reaction is nucleophilic attack at a nitrile followed by cyclization to an extended conjugated structure 24. 25 This means that the thermal stability of the copolymers will increase upon incorporation of AN. Our results are in agreement.…”
Section: Resultsmentioning
confidence: 90%